DETERMINASI MINAT INVESTASI MAHASISWA AKUNTANSI DI KOTA BATAM - Kevin Edly; Neni Marlina Br Purba (LPPM Universitas Putera Batam, 2025)
This study aims to examine the influence of Capital Market Education, Investment Knowledge, and Investment Benefits on Investment Interest among Accounting Students in Batam City. The research is based on the low level of student participation in investment activities, suspected to be caused by a lack of education, knowledge, and understanding of investment benefits. Data were collected using Google Forms from a population of 1,572 accounting students, with a sample of 319 selected through stratified random sampling. Data analysis involved descriptive analysis, data quality tests, classical assumption tests, multiple linear regression, and hypothesis testing using SPSS version 26. The results show that Capital Market Education, Investment Knowledge, and Investment Benefits have a significant effect on students' Investment Interest. Capital Market Education serves as a foundation for understanding the investment world, Investment Knowledge reflects individual mastery of investment mechanisms, risks, and strategies, while Investment Benefits influence students’ perception of the long-term value and advantages of investing